Youth Of Uzbekistan: The Socio-Political Activity - Nilufar Zakirovna Abdumalikova (Genius Journals, 2021)
Strengthening the idea of national ideology in the period of radical social changes in the country is inextricably linked with the process of national identity of the Uzbek people, national identity, the growth of political culture - a progressive phenomenon, an important achievement of national independence. At present, the socio-economic essence of the Uzbek people's development, its spiritual activity has become a key factor in the search for ways of national awakening, development and improvement of national identity, which will become a powerful force only if they know and understand the history, culture and spirituality.
Keywords: National; political culture; activity; social development.